2010
DOI: 10.1002/cm.20454
|View full text |Cite
|
Sign up to set email alerts
|

Centrioles are freed from cilia by severing prior to mitosis

Abstract: Cilia are necessary for normal tissue development and homeostasis and are generally present during interphase, but not in mitosis. The precise mechanism of pre-mitotic ciliary loss has been controversial, with data supporting either sequential disassembly through the transition zone or, alternatively, a severing event at the base of the cilia. Here we show by live cell imaging and immunofluoresence microscopy that resorbing flagella of Chlamydomonas leave remnants associated with the mother cell wall. We postu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 24 publications
1
43
0
1
Order By: Relevance
“…In Chlamydomonas, the flagella generally resorb prior to mitosis (Parker et al, 2010), and in mitosis, the basal bodies migrate close to the poles of the microtubules making up the mitotic spindle (O'Toole and Dutcher, 2014). Parallel cortical arrays of microtubules in interphase give way to microtubules lining the cytokinetic cleavage site (Johnson and Porter, 1968;Piasecki et al, 2008;Mittelmeier et al, 2013).…”
Section: Regulation Of Microtubules During Mitosismentioning
confidence: 99%
“…In Chlamydomonas, the flagella generally resorb prior to mitosis (Parker et al, 2010), and in mitosis, the basal bodies migrate close to the poles of the microtubules making up the mitotic spindle (O'Toole and Dutcher, 2014). Parallel cortical arrays of microtubules in interphase give way to microtubules lining the cytokinetic cleavage site (Johnson and Porter, 1968;Piasecki et al, 2008;Mittelmeier et al, 2013).…”
Section: Regulation Of Microtubules During Mitosismentioning
confidence: 99%
“…HEF1, a transducer of integrin-initiated attachment, migration, and antiapoptotic signals at focal adhesions, appears to be required to stabilize and activate Aurora A for cilia disassembly (Pugacheva et al 2007). In Chlamydomonas, cilia are cleaved from the basal body at the distal end of the transition zone (Parker et al 2010) in a process requiring the scaffold protein Fa1, the NIMA family kinase Fa2 (Finst et al 1998(Finst et al , 2000Mahjoub et al 2002), and the microtubule-severing protein katanin (Quarmby 2000). The…”
Section: The Cilium Cyclementioning
confidence: 99%
“…In the green alga Chlamydomonas, several studies have suggested that katanin plays a role in the flagellar autotomy response to stress and in the release of basal bodies from the transition zone prior to mitosis (Lohret et al, 1998;Lohret et al, 1999;Rasi et al, 2009;Parker et al, 2010). We have shown that Chlamydomonas mutants with defects in the p80 subunit of katanin have no defects in mitosis or flagellar autotomy; rather, these mutants lack the central pair of microtubules (Dymek et al, 2004).…”
Section: Introductionmentioning
confidence: 70%
“…RFLPs are present in the three mutants, indicating the APHVIII gene inserted into a different site in the genome for each mutant. that this severing activity occurs following flagellar resorption and prior to cell division (Parker et al, 2010). Using anti-acetylated atubulin antibodies, immunofluorescence microscopy revealed the presence of two bright dots near recently divided cells, but which had not yet hatched from the mother cell wall.…”
Section: Journal Of Cell Sciencementioning
confidence: 99%
See 1 more Smart Citation